HUKUM PERDATA DI ERA DIGITAL: ADAPTASI, TANTANGAN DAN INOVASI - Ailsa Novelita Saharany (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This article discusses the development of civil law in the digital era, highlighting the challenges and opportunities that arise as a result of technological transformation. In the context of globalization and advances in information technology, civil law is facing significant changes, especially in terms of contracts, personal data protection and dispute resolution. This research analyzes how civil law can adapt to increasingly digital-based business practices, including e-commerce and online transactions. In addition, this article explores the regulations needed to protect individual rights in the digital environment, as well as the importance of collaboration between government, business and society in creating a responsive legal ecosystem. With an analytical approach, this article provides recommendations for legal reform that supports justice and legal certainty in the digital era.